Complementary insects - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The fight against fruit flies (Ceratitis capitata) has entered a new stage. The flies lay their eggs inside ripe fruits and are thus a major pest for fruit growers in the tropics and subtropics. A new combination of two known techniques has turned...